Toxicological evaluation of protein powder derived from Cupriavidus necator - Modica, Vickie; Glávits, Róbert; Murbach, Timothy S.; Endres, John R.; Hirka, Gábor; Vértesi, Adél; Béres, Erzsébet; Pasics Szakonyiné, Ilona (Journal of applied toxicology, 2023)
Microorganisms have the potential to produce nutrient‐rich products that can be consumed as food or feed. The protein‐rich powder derived from heat treatment of the whole‐cell biomass of polyhydroxybutyrate‐deficient Cupriavidus necator, a metabolically versatile organism that uses elements found in the air, is an example of such a product. To assess the safety of the protein powder for use as a nutritional ingredient in human food, in accordance with internationally accepted standards, its genotoxic potential and repeated‐dose oral toxicity were investigated. A bacterial reverse mutation test, an in vitro mammalian chromosomal aberration test, and an in vivo mammalian micronucleus test were performed. No evidence of mutagenicity or genotoxicity was found. Additionally, a 90‐day repeated‐dose oral toxicity study in rats was completed, in which a total of 100 male and female Wistar rats were exposed by gavage to daily doses of 1000, 2000, or 3000 mg/kg bw/day of the test material. Following 90 days of continuous exposure, no mortality or treatment‐related adverse effects were observed and no target organs were identified. Therefore, a no observed adverse effect level was determined at 3000 mg/kg bw/day, the highest dose tested. The whole‐cell biomass of polyhydroxybutyrate‐deficient Cupriavidus necator is protein rich. The derived protein concentrate has the potential for use as an environmentally sustainable nutrient‐dense food ingredient. Therefore, we assessed the genotoxic potential and oral toxicity of the heat‐treated and powdered product, in preclinical safety studies. No evidence of genotoxicity or mutagenicity was found. In a 90‐day repeated‐dose oral toxicity study, a no observed adverse effect level in rats of 3000 mg/kg bw/day, the highest feasible dose, was determined.